Residents’ Perceptions of Impending Forced Relocation in Urban China: A case study of state-led urban redevelopment in Shenyang - Li, Xin (A+BE | Architecture and the Built Environment, 2018)
Since 1978, urban redevelopment in China has resulted in large-scale neighbourhood demolition and forced residential relocation, which can severely disrupt established people-place interactions in the demolished neighbourhoods. Urban redevelopment in China has also been criticized by the public and scholars, because the position of the residents in decision-making processes of urban redevelopment is often marginalized. Conflicts have arisen between the residents, local governments and developers, against the backdrop of the uneven redistribution of capital accumulated via urban space reproduction such as the replacement of declining neighbourhoods in which low-income residents reside, with newly-build high-rise dwellings for middle- or high-income residents (Qian and He 2012, Weinstein and Ren 2009). The aim of the thesis is to gain a deeper understanding of the influence of urban redevelopment and its induced forced relocation on residents, by investigating their behavioural and emotional responses to the state-led urban redevelopment in Shenyang, a Chinese city. In particular, it highlights the agency of the affected residents, through exploring their interactions with other stakeholders and through displaying the ambivalence embedded in their neighbourhood experiences. The research firstly conceptualises forced relocation as a process and as a specific type of residential mobility that occurs in the context of urban restructuring. It suggests a conceptual model to show the sequence of events that households experience during urban redevelopment, by dividing forced relocation into three stages: the pre-demolition stage, the transitional stage and the post-relocation stage (chapter 2). This conceptual model helps to reduce the distraction caused by the accumulation of the dynamics of relocatees’ experience as the urban redevelopment proceeds over time, by capturing the sequence of the events that occur to relocatees during urban redevelopment. We used the model to structure the analysis of the literature review and subsequently identify the gaps in the literature that should be addressed in future forced relocation studies about China. We discovered that the experiences of relocatees from household and residential mobility perspectives reveal the dynamic, variable and complex nature of forced relocation, which makes forced relocation in urban China not necessarily equivalent to displacement. We particularly targeted at the residents who are undergoing the pre-demolition stage of state-led national scale Shantytown Redevelopment Projects (SRPs) in Shenyang, a city in Northeast China. Since 2008, the central government has initiated SRPs to improve the living conditions of low-income residents living in declining neighbourhoods. Between 2008 and 2012, about 12.6 million households in China were involved in SRPs, and forced to move as their dwellings were demolished. These residents are stayed homeowners living in declining danwei communities and urban villages. They are among one of the most deprived social groups due to unemployment, low-income, serious illness etc., and cannot afford better dwellings. We found that (prospective) relocatees’ experiences at this stage are worthwhile to study. Their experiences and compensation choices at this stage can affect their follow-up housing experiences, since they need to make significant decisions with regard to the type and the amount of compensation (in-kind or monetary) that they can get from local governments and/or developers. However, current studies mainly target the relocatees who are already at the post-relocation stage to recall their pre-relocation experiences to evaluate the outcomes of forced relocation, which might lead to distorted retrospective accounts of their experiences and causes of their behavioural and emotional responses to the forced relocation (Goetz, 2013; Higgins and Stangor, 1998). This pre-relocation stage is also the most stressful and conflicting stage for the relocatees involved in urban redevelopment and forced relocation. It is the stage that includes land expropriation, compensation negotiations and forced movement, after intensive interactions between residents and other stakeholders. In chapter 3, we discuss a complex interplay between different stakeholders, by focusing the implementation of SRPs and the changing roles of different stakeholders. Conflicts arise between different stakeholders, featured by frictions between the central and local governments regarding the implementation of SRPs, the mismatch occurs between the scope of the SRP policy and residents’ attempts to improve their socioeconomic situation, and an entrepreneurial paradox in the relationship between local governments and developers. However, we also discovered that various stakeholders have consensus on the need for improving the living conditions in deprived neighbourhoods and on boosting the housing market. In particular, by displaying the consensus between residents, local governments and developers, we reveal the agency of residents during urban redevelopment (see also Manzo et al., 2008; Posthumus and Kleinhans, 2014). To a certain extent, residents are willing to accept urban redevelopment and forced relocation to improve their living conditions. They also intend to maximize their benefits from the redevelopment, by mobilising strategies such as constructing illegal buildings to improve the overall value of their dwelling, or by making appeals to local governments to intervene in the redevelopment (chapter 4). In addition, this research investigates the interaction between people (residents) and place (neighbourhoods) from the perspective of place attachment and ageing in place, to show the influences of urban redevelopment and forced relocation on the residents. By revealing the lived experiences of homeowners and older people in danwei communities and urban villages, we found that residents have ambivalent attitudes towards forced relocation and urban redevelopment. On the one hand, these residents anticipate a potential improvement of their living conditions via SRPs, because neighbourhood decline has been challenging their daily activities and decreasing their quality of life for years. From a people-place interaction point of view, this might be contradicting earlier research which emphasizes the more ‘romantic’ side of people-place interactions, such as place attachment and its related components (e.g. neighbourhood-based social networks and mutual help), that contribute to relocatees’ willingness to stay in their neighbourhoods when facing neighbourhood redevelopment and demolition (Fried, 1963; Manzo et al., 2008). On the other hand, many homeowners and older people are unwilling to move, since their current neighbourhood makes them feel rooted and enables them to develop living strategies to relieve their deprived socio-economic situation. Therefore, we suggest that when studying the influence of urban redevelopment on relocatees, the wider impacts of place attachment on their moving behaviour should be revealed by carefully examining their positive and negative lived experiences and the roles of different dimensions of place attachment (Livingston et al., 2010; Oakley et al., 2008; Vale, 1997). Based on the aforementioned findings, several directions for the future research can be proposed. Firstly, more research on temporal changes of individual perceptions and experiences during and after urban redevelopment is needed. In particular, we propose to conduct a longitudinal panel survey following relocatees from the three stages to identify how and why forced relocation and urban redevelopment affect the well-being of the relocatees over time and how the outcomes of relocation vary over time. Second, the heterogeneity of the affected residents and the interrelationship of this heterogeneity with their experiences should also be addressed more specifically in future research. Finally, in addition to the declining urban neighbourhoods such as danwei communities, inner city old neighbourhoods and urban villages, other types of neighbourhoods involved in Shantytown Redevelopment Projects (SRPs) should be a focus of research, for example remote rural communities established by state-owned enterprises and enterprises specialised in mining, agricultural and forestry production. We suggest that more comparative studies should be conducted with regard to governance of SRPs and its influence on the relocatees from different regions and cities across China. Our research findings can be useful for the central state and local governments to recognize the problems existing in SRPs, such as the disparity between the project scope and the expectations of the residents, the ignorance of the diverse needs of the affected residents, and the uncertainties and related negative influence on the residents in relation to the project implementation. We suggest local governments to consider the physical, social, economic and psychological influences of urban redevelopment on residents. In particular, the research suggests local governments to carefully design the compensation policy, which concerns the relocatees the most. The compensation criteria should cover various needs of relocatees regarding rehousing, such as dwelling size, nearby public and commercial facilities, and job opportunities. Local governments need to better investigate the socio-economic and family situations of affected residents before the redevelopment and forced relocation, since the needs and the expectations of different relocatees about redevelopment differ as well.